Infant Iodine and Selenium Status in Relation to Maternal Status and Diet During Pregnancy and Lactation - Stråvik, Mia; Gustin, Klara; Barman, Malin; Skröder, Helena; Sandin, Anna; Wold, Agnes E.; Sandberg, Ann-Sofie; Kippler, Maria; Vahter, Marie (Frontiers in Nutrition, 2021)
Iodine and selenium are essential trace elements. Recent studies indicate that pregnant and lactating women often have insufficient intake of iodine and selenium, but the impact on fetal and infant status is unclear. Here, we assessed iodine and selenium status of infants in relation to maternal intake and status of these trace elements in the birth cohort NICE, conducted in northern Sweden (n=604). Iodine was measured in urine (UIC) in gestational week 29, and in breast milk and infant urine four months postpartum, while selenium was measured in maternal plasma and erythrocytes in gestational week 29, and in breast milk and infant erythrocytes four months postpartum, in both cases using ICP-MS. Maternal intake was assessed with semi-quantitative food frequency questionnaires in gestational week 34 and at four months postpartum. The median intake of iodine and selenium during pregnancy (98 and 40 µg/d, respectively) and lactation (108 and 39 µg/d, respectively) was below recommended intakes, reflected in insufficient status (median UIC of 113 µg/L, median plasma selenium of 65 µg/L). Also, breast milk concentrations (median iodine 77 µg/L, median selenium 9 µg/L) were unlikely to meet infant requirements. Median UIC of the infants was 114 µg/L and median erythrocyte selenium 96 µg/kg, both similar to the maternal concentrations. Infant UIC correlated strongly with breast milk levels (rho=0.64, p<0.001). Their erythrocyte selenium correlated with maternal erythrocyte selenium in pregnancy (rho=0.38, p<0.001), but not with breast milk selenium, suggesting formation of prenatal reserves. Our results indicate that the transport of iodine and selenium to the fetus and infant is prioritized. Still, it is uncertain whether most infants had sufficient intakes. Further, the results might indicate an involvement of iodine in asthma development during the first year of life, which is essential to follow up. The low maternal and infant dietary intake of both iodine and selenium, especially when the mothers did not use supplements or iodized table salt, suggest a need for a general screening of women and young children.